Exploring drivers of pre-exposure prophylaxis uptake among gay, bisexual, and other men who have sex with men in Malaysia. (August 2022) - Eger, William H; Adaralegbe, Adeleye; Khati, Antoine; Azwa, Iskandar; Wickersham, Jeffrey A; Osborne, Sydney; Shrestha, Roman
Background: Pre-exposure prophylaxis (PrEP) is a valuable HIV prevention strategy, particularly among men who have sex with men (MSM); however, PrEP uptake is below the threshold needed to curb the HIV epidemic among this group, especially in settings like Malaysia, where same-sex sexual behavior is illegal. Methods: A sample of 355 participants completed an online survey between June and July 2020, recruited through geosocial networking apps for MSM and social networking websites (e.g. Facebook). We used descriptive and multivariable analyses to examine correlates of PrEP use within this population. Results: The sample was predominantly Malay (53.5%), had monthly incomes greater than RM 3000 (USD 730) (52.7%), and a tertiary level of education (84.5%). About 80% of participants heard of PrEP prior to the survey, with significantly less (18.3%) having ever taken PrEP. In the adjusted multivariable logistic model, using drugs before or during sexual intercourse ("chemsex") (AOR: 3.37; 95% CI: 1.44–7.89), being diagnosed with a sexually transmitted infection in the last 12 months (AOR: 2.08; 95% CI: 1.13–3.85), HIV testing in the previous 6 months (AOR: 3.23; 95% CI: 1.74–5.99), and disclosure of sexual orientation (AOR: 1.85; 95% CI: 1.02–3.34) were associated with having taken PrEP in the past. Conclusions: This study revealed that PrEP use among Malaysian MSM is relatively low, despite high awareness, and is associated with healthcare engagement and high-risk behaviors. These results highlight the need to tailor outreach activities for individuals at increased risk for HIV and those disengaged with the health system.